ESTIMATED MODEL OF URBAN LAND VALUE TOWARDS SINGLE VALUE FOR MULTIPURPOSE - Trianawati Sugito, Nanin
The urban land value estimation model is a mathematical model to estimate the value of land in urban areas. Until now, there is no accurate land value estimation model that can be used as a reference for various purposes. A single value for multiple purposes is known as a single value for multipurpose, which is a single reference value that can be used as a reference for various needs.